PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) DAN REGISTRASI ONLINE BERBASIS WEBSITE PADA SMP NEGERI 6 PALANGKA RAYA - Enny Dwi Oktaviyani; Dilla Ayu Dwipitaloka; Felicia Sylviana; Licantik Licantik (Universitas Palangka Raya, 2020)
SMP Negeri 6 Palangka Raya has a new student admission activity every year. The Implementation of New Student Admissions for SMP Negeri 6 Palangka Raya is a routine activity to recruit prospective new students who come from elementary or MI. So far, it is known that at SMP Negeri 6 Palangka Raya, the system for accepting new students and re-registering new students is still done manually, namely prospective students come to school with the registration requirements in the form of a Certificate of Original National Graduation Result, a copy of the Family Card, and a photo This makes the registration of new students and re-registration is ineffective and inefficient, because a lot of time, money and energy is wasted to register as new students and re-register at the school. Therefore we need a reliable, effective and efficient system that makes it easy for prospective new students who wish to register at the school and re-register when it is accepted to be accepted at the school, and also makes it easy for schools and committees in managing data of prospective new students quickly and efficiently and making credible reports, so that new student registration can be carried out properly The software development method used is a waterfall, system analysis using data flow diagrams and entity relationship diagrams, program code using PHP and MySQL. Based on the results of testing using the blackbox, the new student admission information system can be used properly